Costs of adverse events associated with erlotinib or afatinib in first-line treatment of advanced EGFR-positive non-small cell lung cancer - Isla, Dolores (Clinicoecon Outcomes Res, 2016)
OBJECTIVES: Epidermal growth factor receptor–tyrosine kinase inhibitors (EGFR-TKIs) are an established treatment for advanced non-small cell lung cancer (NSCLC) with EGFR mutation. According to published meta-analyses, no significant efficacy differences have been demonstrated between erlotinib and afatinib. However, the incidence of EGFR–TKI-related adverse events (AEs) was lower with erlotinib. This study compares the cost of management of the AEs associated with these two drugs from the perspective of the Spanish National Health System (NHS). METHODS: The frequency of AEs was established from a recently published meta-analysis. In Spain, the daily cost of both drugs can be considered similar; as a result, only the costs of management of the AEs were considered. Costs and resource utilization in the management of the AEs were estimated by a panel of Spanish oncologists and from studies previously carried out in Spain. A probabilistic analysis was performed based on a Monte Carlo simulation. RESULTS: The model generated 1,000 simulations. The total cost per patient treated with erlotinib and afatinib was €657.44 and €1,272.15, respectively. With erlotinib, the cost per patient and per AE of grades ≤2 and ≥3 was €550.86 and €106.58, respectively, whereas the cost with afatinib was €980.63 and €291.52, respectively. The reduction in the number of AEs with erlotinib could avoid a mean cost for the NHS of €614.71 (95% CI: €342.57–881.29) per patient. CONCLUSION: In advanced EGFR mutation-positive NSCLC patients, first-line treatment with erlotinib could reduce health care costs for the NHS, due to a decrease in the AE rate compared with afatinib. In long-term treatments, the avoidance of complications and the lowering of costs associated with the management of AEs are relevant factors that contribute to the sustainability of the health system.